2018
DOI: 10.21037/jgo.2018.09.08
|View full text |Cite
|
Sign up to set email alerts
|

Daily breathing inconsistency in pancreas SBRT: a 4DCT study

Abstract: Background: Stereotactic body radiation therapy (SBRT) treatments of pancreatic cancer typically employ relatively small margins. This study characterizes the motion of high visibility structures in close proximity to the pancreas to determine how much the motion envelope of such a structure changes due to respiratory variation between fractions. Methods: Fanbeam, four-dimensional computed tomography (4DCT) studies acquired initially for planning and again prior to each treatment for 6 patients were used to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of a study on 4DCT of pancreatic tumors by Sarkar et al. showed the daily breathing inconsistency in the pancreas SBRT ( 23 ). This further indicated that the isotropic ITV edge expansion may not be appropriate because it cannot be fully considered the movement of inter- and intra-fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study on 4DCT of pancreatic tumors by Sarkar et al. showed the daily breathing inconsistency in the pancreas SBRT ( 23 ). This further indicated that the isotropic ITV edge expansion may not be appropriate because it cannot be fully considered the movement of inter- and intra-fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Gastrointestinal Oncology. For example, giving the best care possible may mean paying extra attention to radiation therapy planning to avoid unnecessary toxicity as exemplified by the analysis of the effect that breathing differences can have on radiation target coverage by Sarkar and colleagues (12). It may mean combing through big data to discover clues as to most successful real world practice patterns (13).…”
mentioning
confidence: 99%